Si3N4@RGO Hybrids for Epoxy Coatings With Enhanced Anticorrosion Performance. Issue 5 (4th December 2018) - Ge, Heyi; Wang, Ting; Cheng, Shilin
Abstract : The reduced graphene oxide (RGO)‐encapsulated functionalized silicon nitride hybrids (f‐Si3 N4 @RGO) were fabricated from sodium borohydride reduction of electrostatically assembled f‐Si3 N4 @GO hybrids with the help of silane coupling agent. The waterborne epoxy coating with 2 wt% f‐Si3 N4 @RGO was prepared by a room temperature curing process. The corrosion resistance properties of the coating were investigated. In the f‐Si3 N4 @RGO/epoxy coating, the unique structure of f‐Si3 N4 particles firmly embedded in the RGO sheets could effectively prevent the agglomeration of graphene in the epoxy and construct shielding barrier at the coating‐tinplate interface. The results showed that the anticorrosive performance of the coating was significantly enhanced by incorporation of f‐Si3 N4 @RGO hybrids to epoxy. This superior f‐Si3 N4 @RGO structure with its prominent dispersion could make full use of the enhancement effect of the different components and thus endowed the waterborne epoxy coating with good shielding properties. POLYM. COMPOS., 2018. © 2018 Society of Plastics Engineers